Readings in microfinance : reach and impact - Osmani, Siddiqur Rahman; Khalily, M. A. Baqui; Institute of Microfinance (Bangladesh); Great Britain. Dept. for International Development (Dhaka : University Press : UKaid from the Dept. for International Development, 2011)
Contributed articles.
Includes bibliographical references.
Complimentary copy from Professor Dr. Nasreen Khundker
Keywords: Microfinance -- Bangladesh; Microfinance -- Bangladesh -- Case studies